ZrBr4-Mediated Phase Engineering in CsPbBr3 for Enhanced Operational Stability of White-Light-Emitting Diodes - Muhammad Amin Padhiar; Yongqiang Ji; Jing Wang; Noor Zamin Khan; Mengji Xiong; Shuxin Wang (Nanomaterials)
The persistent operational instability of all-inorganic cesium lead halide (CsPbX3) perovskite nanocrystals (NCs) has hindered their integration into white-light-emitting diodes (WLEDs). This study introduces a transformative approach by engineering a phase transition from CsPbBr3 NCs to zirconium bromide (ZrBr4)-stabilized hexagonal nanocomposites (HNs) through a modified hot-injection synthesis. Structural analyses revealed that the ZrBr4-mediated phase transformation induced a structurally ordered lattice with minimized defects, significantly enhancing charge carrier confinement and radiative recombination efficiency. The resulting HNs achieved an exceptional photoluminescence quantum yield (PLQY) of 92%, prolonged emission lifetimes, and suppressed nonradiative decay, attributed to effective surface passivation. The WLEDs with HNs enabled a breakthrough luminous efficiency of 158 lm/W and a record color rendering index (CRI) of 98, outperforming conventional CsPbX3-based devices. The WLEDs exhibited robust thermal stability, retaining over 80% of initial emission intensity at 100 °C, and demonstrated exceptional operational stability with negligible PL degradation during 50 h of continuous operation at 100 mA. Commission Internationale de l’Éclairage (CIE) coordinates of (0.35, 0.32) validated pure white-light emission with high chromatic fidelity. This work establishes ZrBr4-mediated HNs as a paradigm-shifting material platform, addressing critical stability and efficiency challenges in perovskite optoelectronics and paving the way for next-generation, high-performance lighting solutions.